Erythrocyte membrane affinity chromatography, solid-phase extraction and UPLC-QTOF-MS/MS to screen active ingredients of Buyang Huanwu decoction. Issue 50 (17th September 2019) - Yu, Aiming; Zheng, Huazhu; Yan, Xiangli; Wang, Shengxin; Shen, Xiao; Zheng, Haozhen; Meng, Yingjiao; Wang, Lisheng
Abstract : A method that uses erythrocyte membrane and solid-phase extraction to isolate the specific compounds of Buyang Huanwu decoction was developed. Abstract : Buyang Huanwu decoction (BHD) is a well-known traditional Chinese medicine that has long been used to treat ischemic brain damage which is associated with hemorheology. To screen active ingredients in BHD responsible for reducing blood viscosity by reducing red blood cell (RBC) lesions to treat ischemic stroke, a method involving RBC membrane binding and solid-phase extraction (SPE) was developed in this study. The components of BHD interacting with RBC were analyzed by mass spectrometry and four compounds, calycosin, paeoniflorin, 6-hydroxy behenol-3, 6-di- O -glucoside and calycosin-7- O -β-d -glucoside, showed binding affinity to RBCs. An erythrocyte activity assay revealed that the identified ingredients promoted the activities of Na + -K + -ATPase, sialic acid and superoxide dismutase and reduced the content of cholesterol on the RBC membrane, suggesting a mechanism underlying their anti-erythrocyte aggregation activity. Based on these results, the RBC membrane binding assay combined with SPE and mass spectrometry is a novel and effective approach for screening potentially anti-erythrocyte lesion constituents in traditional Chinese medicines.